Success and failure of reindeer herding in Greenland - Cuyler, Christine (1999)
Animal husbandry is a recent innovation in Greenland, specifically reindeer husbandry is less than 50 years old. Reindeer husbandry was first introduced to mid-west Greenland and later in southern Greenland. The Greenland hunter tradition and culture is, however, dominant in many communities.